Environmental tobacco smoke exposure in children in two districts of the Czech Republic - Dostál, Miroslav; Milcová, Alena; Binková, Blanka; Kotesovec, Frantisek; Nozicka, Jirí; Topinka, Jan; Srám, Radim J (International journal of hygiene and environmental health, 2008)
In the course of epidemiologic studies on the health of preschool children in the Teplice and Prachatice districts of the Czech Republic, we have recorded the frequency of smokers in the families of the children under study and the exposure of the children to environmental tobacco smoke (ETS) by assaying urinary cotinine levels. Questionnaires were administered at the age of 3 years (children born 1994-1996) or 4.5 years (children born 1997-1998). Out of 1128 respondents, 35.6% of the mothers and 48.9% of their husbands/partners were smokers. Taking into account other adult smokers, 41.6% of children lived in households without smokers and 30.1% in households with one smoker. There were more smokers among both mothers and fathers in Teplice than in the Prachatice district (mothers: 41.1% vs. 28.5%, P=0.017; fathers: 50.8% vs. 46.5%, NS). Cotinine concentration in the urine was determined using a radioimmunoassay in 523 pairs of mothers and children at the age of 4.5 years. A level higher than 500 ng cotinine per mg creatinine (our cut-off for active smoking) was detected in 199 out of 523 mothers (38%). Using 20 ng/mg as the cut-off, 48.2% of 523 children were exposed to ETS. There were more ETS-exposed children in Teplice than in the Prachatice district (59.2% vs. 34.7%, P<0.001). When cotinine levels were measured in 479 of these children at the age of 6-7 years, the percentage of children exposed to ETS decreased to 36.5%. However, the difference between Teplice and Prachatice children persisted (44.6% vs. 27.8%). Our results suggest that in the Czech Republic, children under 5 years of age are significantly exposed to tobacco smoke and that more effective regulatory measures are needed to decrease the prevalence of smoking.
Keywords: kouření; Smoking; biologické markery; následné studie; lidé; Adult; látky znečišťující vzduch; matky; Mothers; Tobacco Smoke Pollution; znečištění vzduchu ve vnitřním prostředí; otcové; Female; dítě; průzkumy a dotazníky; Humans; Air Pollution, Indoor; Follow-Up Studies; Air Pollutants; Česká republika; předškolní dítě; Cotinine; Child, Preschool; Biomarkers; logistické modely; mužské pohlaví; znečištění tabákovým kouřem; ženské pohlaví; kotinin; Czech Republic; Logistic Models; Male; Fathers; Child; dospělí; Surveys and Questionnaires